Chicken Coop Monitoring System using You Only Look Once (YOLO) Algorithm - Rahman, Omar Fauzi; Erlina, Tati (Universitas Andalas, 2026)
As chicken meat production increases in Padang City, farmers face serious threats from predators and intruders that cause significant losses. Current solutions, such as PIR motion detectors, have the disadvantage of not being able to recognize the objects they detect. This study designs a chicken coop monitoring system capable of identifying objects using the You Only Look Once (YOLO) algorithm. The system uses a Raspberry Pi 4 Model B as the processing center, connected to two Arducam OV5647 cameras mounted on MG996R servo motors. The system is also integrated with a Telegram application for real-time notifications. Based on testing, the system is capable of detecting and classifying objects with an average accuracy of 83.26% and an average notification response time of 10.8 seconds. Thus, the system is effective in addressing security issues in chicken farms